CULTURE OF “DELO TOMBOWA LO TABO WAU LABIYA” IN CAPITAL ACCOUNTING PRACTICES BY ILABULO TRADERS - Thalib, Mohamad Anwar (Jurnal Al-Iqtishad, 2023)
This study aims to construct capital accounting practices by ilabulo traders based on local cultural values. This research uses the Islamic paradigm. The approach used is Islamic ethnomethodology. There are five data analysis stages: charity, knowledge, faith, revelation information, and courtesy. The results showed that the capital used by ilabulo traders came from personal funds, gifts from husbands, and parental loans. This practice of capital accounting lives on in the spirit of cooperation among families. This value is reflected in the actions of the husband, who provides both material and non-material support to his wife to trade ilabulo, parents, who provide unsecured money loans, flexible debt repayment terms, and no interest on loans. In the Islamic culture of Gorontalo, the value of cooperation is often advised by the elders through lumadu "delo tombowata lo tabo wau labiya" which means like a mixture of fat and sago. This expression stirs up the meaning of a sakinah household life.” The implication of this research is to present the concept of capital accounting, not only material but conditions with non-material values in the form of local culture and religiosity.